Choice Inconsistencies among the Elderly: Evidence from Plan Choice in the Medicare Part D Program - Abaluck, Jason; Gruber, Jonathan (American Economic Review, 2011)
We evaluate the choices of elders across their insurance options under the Medicare Part D Prescription Drug plan, using a unique data set of prescription drug claims matched to information on the characteristics of choice sets. We document that elders place much more weight on plan premiums than on expected out of pocket costs; value plan financial characteristics beyond any impacts on their own financial expenses or risk; and place almost no value on variance reducing aspects of plans. Partial equilibrium welfare analysis implies that welfare would have been 27% higher if patients had all chosen rationally.